Deciphering the Biodiversity–Production Mutualism in the Global Food Security Debate. (November 2020) - Seppelt, Ralf; Arndt, Channing; Beckmann, Michael; Martin, Emily A.; Hertel, Thomas W.
Abstract : Without changes in consumption, along with sharp reductions in food waste and postharvest losses, agricultural production must grow to meet future food demands. The variety of concepts and policies relating to yield increases fail to integrate an important constituent of production and human nutrition – biodiversity. We develop an analytical framework to unpack this biodiversity-production mutualism (BPM), which bridges the research fields of ecology and agroeconomics and makes the trade-off between food security and protection of biodiversity explicit. By applying the framework, the incorporation of agroecological principles in global food systems are quantifiable, informed assessments of green total factor productivity (TFP) are supported, and possible lock-ins of the global food system through overintensification and associated biodiversity loss can be avoided. Highlights: Increasing demands for agricultural commodities are resulting in more intensely managed landscapes. This is at odds with biodiversity conservation and largely ignores farmland biodiversity's supporting function for high and stable yields. An overhaul of agroeconomic models to account for the biodiversity-production mutualism is urgently needed to answer a question of utmost importance: How do we manage the resources of our planet in such a way that we produce enough healthy food without destroying our life-support system? A comprehensive analytical framework is provided that accounts for multitrophic biodiversity-production processes; bridges disciplinary boundaries between agronomy, agroecology, economics, and conservation science; and elucidates the strong interactions of ecosystem functioning with food security and malnutrition.